ANALISIS FAKTOR – FAKTOR PENYEBAB MASALAH PUTUS OBAT PADA PROGRAM KONTROL TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS GERUNG LOMBOK BARAT - Zulkifi Zulkifi; Hadi Kusuma Atmaja; Awan Dramawan (poltekkes kemenkes mataram, 2014)
Abstract: Health development as part of the national development implemented gradually and continuously, and is intended to improve the welfare of the people as a whole. One part of health development is the implementation of infectious disease eradication program. Pulmonary Tuberculosis in the world situation gets worse by the number of cases continues to rise and many are not successfully treated, especially countries that are grouped in 22 countries with Pulmonary Tuberculosis big problem (high-burden countries), so that in 1993 the WHO declared as one of Pulmonary Tuberculosis emergency one of the world (global emergency). The purpose of this study was to determine the factors that cause medication discontinuation problems in tuberculosis control programs. Design used in this study is to approach Retrospective Cross Sectional Study. The population in this study were all patients with TB who enter the working area of Public Health Center Registration Gerung West Lombok. The research sample consists of 10 respondents. The independent variables are factors that cause the problem of drug withdrawal and the dependent variable is the TB patients who drop out of medicine. Data obtained using quisioner. The results of this study indicate that the psychological burden on the majority of TB patients who drop out of medicine and the treatment of TB patients showed a majority of respondents felt unable to reduce the disease during consumption of drugs, and most respondents felt forced to discontinue treatment because of resistance in drug consumption, but they feel no difficulty in the treatment and feel they have support from family and health workers.